Development and Validation of the Nomograms for Predicting Overall Survival and Cancer-Specific Survival in Patients With Synovial Sarcoma - Song, Zhengqing; Cheng, Lisha; Lu, Lili; Lu, Weiqi; Zhou, Yuhong; Wang, Zhiming (Frontiers in Endocrinology, 2022)
Background: The study aimed to build and validate practical nomograms to predict overall survival (OS) and cancer-specific survival (CSS) for patients with synovial sarcoma (SyS). Methods: A total of 893 eligible SyS patients diagnosed between 2007 and 2015 were identified in the SEER database. Patients were randomly divided into the training cohort (n=448) and validation cohort (n=445). Clinically independent prognostic and important factors were determined and selected according to the Akaike information criterion in multivariate Cox regression models when developing the nomograms with the training cohort. The predictive accuracy of nomograms was bootstrapped validated internally and externally with the concordance index (C-index) and calibration curve. Decision curve analysis (DCA) was performed to compare the clinical usefulness between nomograms and AJCC staging system. Results: Two nomograms shared common indicators including age, insurance status, tumor site, tumor size, SEER stage, surgery, and radiation, while marital status and tumor site were only included into the OS nomogram. The C-index of nomograms for predicting OS and CSS was0.819(0.873-0.764) and 0.821(0.876-0.766), respectively, suggesting satisfactory predictive performance. Internal and external calibration curves exhibited optimal agreement between the nomogram prediction and the actual survival. Additionally, DCA demonstrated that our nomograms had obvious superiority over the AJCC staging system with more clinical net benefits. Conclusions: Two nomograms that could predict 3- and 5-year OS and CSS of SyS patients were successfully constructed and validated for the first time. Our nomograms gained higher predictive accuracy and clinical usefulness than the AJCC staging system in predicting CSS and OS.